Nanowelded Carbon Nanotubes From Field-Effect Transistors to Solar Microcells - Chen, Changxin; Zhang, Yafei (NanoScience and Technology, 2009)
The monograph places emphasis on introducing a novel ultrasonic nanowelding technology of carbon nanotubes (CNTs) to metal electrodes and its application for CNT devices. The structure and electronic property of CNTs, synthesis and purification of CNTs, and the fabrication processes of CNT-based devices etc. are covered in the book. Based on this, the carbon nanotube field-effect transistors (CNTFETs) and photovoltaic (PV) solar microcells fabricated with the ultrasonic nanowelding techniuqe are discussed. The book will be of interest to graduates, scientists and engineers working on CNTs and related topics from both academic and industrial backgrounds.